Nickel speciation in soil and the relationship with its concentration in fruits - Yaman, M (Springer-Verlag, 2000)
Interest in the potential link between cancer and some inorganic nickel compounds (Nriago 1980) has drawn attention to the Ni concentration in food and other environmental samples. The studies of the uptake and chemical behavior of Ni in plants are related mainly to its toxicity having possible implications with respect to animals and man. On the basis of a report published by the International Committee on Nickel Carcinogenesis in Man (ICNCM) (Report 1990), the International Agency for Research into Cancer concluded that (i) there is sufficient evidence to establish a correlation between nickel sulfate and combinations of nickel sulfides and oxides and the incidence of lung and nasal cancers; (ii) there is inadequate evidence to establish a similar correlation for metallic nickel and nickel alloys; and (iii) limited evidence in experimental animals for the carcinogenicity of Ni compounds including metallic nickel, alloys and various nickel salts. The anthropogenic nickel sources of soil are the metal processing operations and the combustion of coal and oil because organic matter reveals a strong ability to absorb Ni; so, this metal is likely to be concentrated in coal and oil. In particular, nickel in sewage sludge that is present mainly in organic chelated forms is readily available to plants and therefore may be highly phytotoxic. The general approach for the soil speciation studies has been to separate the soil into different chemical reagent or solvent fractions and, by analyzing each fraction, to determine the amount of element combined or associated with each soil fraction or phase (Ure 1991). A number of extractants, including ethylenediaminetetraacetic acid (EDTA), diethylenetriamine pentaacetic acid (DTPA), acetic acid, ammonium acetate, calcium chloride and hydroxylamine hydrochloride have been tested to identify metal species as exchangeable, carbonate-bound, Fe and Mn oxide-bound, organically bound, and to estimate the plant available trace metals. Flame atomic absorption spectrophotometry (FAAS) has proved to be a reliable, convenient and rapid method for analysis of toxic and nutritional metals in food, biological and environmental matrices, as direct or, particularly, in combination with preconcentration method (Morales et.al. 1993; Gucer and Yaman 1992; Yaman and Gucer 1994, 1995a, 1995b and 1998; Yaman 1997, 1998 and 1999; Alegria et. al. 1988). In this study, nickel concentrations in the fruit samples were determined by FAAS after preconcentration on activated carbon. Soil samples were dissolved by using the extractants such as the mixture of nitric acid/hydrogen peroxide, oxalic acid, Na(2)EDTA, acetic acid and citric acid and the extracts were analyzed for Ni by using direct FAAS measurements. So, the relation between the fruit nickel contents and the soil extractants-Ni contents was investigated. In addition, the possible chemical forms of Ni in soil were evaluated.
Keywords: Atomic-Absorption Spectrometry; Activated-Carbon Enrichment; Vegetables; Lead; Preconcentration; Vanadium; Matrices; Cadmium